Long life span of tolerant T cells and the role of antigen in maintenance of peripheral tolerance - Alferink, Judith; Schittek, Birgit; Schönrich, Günter; Hämmerling, Günter J.; Arnold, Bernd (International immunology, 1995)
To follow the fate of tolerant T cells in vivowe used a transgenic mouse model in which peripheral T cell tolerance was based on a non-deletional mechanism. These mice expressed two transgenes: the MHC class I molecule Kb under the keratin IV promoter on keratinocytes (2.4 KerlV-Kb) and an anti-Kb TCR identified by the anti-clonotypic antibody Desire-1 (DES-TCR). Although these mice were tolerant to Kb skin grafts, CD8+DES+ T cells were present in their lymphoid organs in the same numbers as in Kbreactive DES-TCR single-transgenic mice. The unresponsiveness towards Kb grafts suggested previous contact of the CD8+DES+ T cells with the Kb molecule on keratinocytes, but the evidence was indirect. The present study demonstrates enhanced levels of activation markers like CD44 and CD2 on the tolerant T cells, indicating contact with the Kb molecule. Continuous presence of antigen was required for maintenance of the tolerant state as shown by transfer of tolerant T cells into Kb-negative nu/nu BALB/c mice. Three days after cell transfer most recipients were still tolerant and accepted Kb-positive skin grafts, but 2 weeks after transfer the transferred cells had recovered their responsiveness and rejected Kb grafts. In order to see if contact with the tolerogen would eventually drive the tolerant cells into cell death, the life span of tolerant CD8+DES+ cells was measured in thymectomized DES-TCR × 2.4 Ker1V-Kb doubletransgenic mice. The tolerant cells were found to have a life span of at least 8 weeks, which was comparable with the life span of non-tolerant CD8+DES+ cells from DES-TCR single-transgenlc mice. Thus, tolerant T cell populations can be long-lived and need continuous contact with the tolerogen to remain tolerant.
Gesehen am 28.07.2025